Context :

Definition : We say $f(x) \in F[x]$ splits over the field extension $E/F$ if $$ f(x) = c (x-\alpha_1)\cdots(x-\alpha_n) $$ for some $c, \alpha_1, \ldots, \alpha_n \in E$. A splitting field of $f$ is a minimal extension $E$ such that $f$ splits over $E/F$.

Theorem: Every polynomial $f(x) \in F[x]$ has a unique splitting field up to isomorphism.

Now, the unicity part of the Theorem is a particular case of the more general result below.

Lemma: Let $\sigma : F \to F'$ be a field isomorphism. For $f(x) = \displaystyle \sum_{i=0}^n a_i x^i \in F[x]$, define $\sigma(f)(x) := \displaystyle \sum_{i=0}^n \sigma(a_i) x^i \in F'[x]$. Let $E$ (respectively $E'$) be a splitting field of $f$ (respectively of $\sigma(f)$). Then, $\sigma$ extends to an isomorphism $\widetilde{\sigma} : E \to E'$.

Indeed, taking $F' = F$ and $\sigma = id_F$ shows that any two splitting fields of $f$ must be isomorphic, whatever $f$ is in $F[x]$.

Now, I struggle with the proof of this Lemma. Basically it goes like this.

Proof of the Lemma: We induct over $n$, the number of roots of $f$ in the splitting field $E$ (there are $\deg f$ such roots, counting multiplicity) that are not in $F$.

If $n=0$, then $E = F$ and since the images of the roots of $f$ are roots of $\sigma(f)$, we also have $E' = F'$. Hence. there is no need to extend $\sigma$.

If $n>0$, let $\alpha \in E \backslash F$ be a root of $f$ and let $m(x)$ be its minimal polynomial over $F$ ($m$ exists since $f(\alpha) = 0$ and $f \in F[x]$). Then we have the following sequence of isomorphisms $$ F(\alpha) \to F[x]/(m(x)) \to F'[x]/(\sigma(m)(x)) \to F'(\alpha'), $$ given by $$ \alpha \mapsto \overline{x} \mapsto \overline{x} \mapsto \alpha', $$ where $\alpha'$ is any root of $\sigma(m)$ in $E' \backslash F'$. Hence by composition we get an isomorphism $\sigma_1 : F(\alpha) \to F'(\alpha')$ extending $\sigma$. Since $f$ has less than $n$ roots in $E \backslash F(\alpha)$, induction completes the proof.

Question: What exactly are the three isomorphisms ? I know that since $\alpha$ is algebraic over $F$, we have $F(\alpha) = F[\alpha]$ and so every element in $F(\alpha)$ can be written $f(\alpha)$ for a certain polynomial $f(x) \in F[x]$, therefore knowing the image of $\alpha$ gives a lot of information about the isomorphism. But what are the elements of $F$ mapped to in the first isomorphism, for example ?

Also how can we see instantly that these are isomorphisms ?


The isomorphism $F(a) \rightarrow F[x]/(m(x))$ just maps $a$ to $x$ (and $F$ to itself).

It's actually easier to show the map the other way is an isomorphism. The map $F[x] \rightarrow F(a)$ mapping $x$ to $a$ is well-defined, and surjective because $F(a) = F[a]$. Its kernel consists of polynomials $p(x) \in F[x]$ such that $p(a)=0$. These are exactly the polynomials that the minimal polynomial $m(x)$ of $a$ divide (by the usual argument of showing the remainder after division is zero by minimality). So the kernel is $(m(x))$ and $F[x]/(m(x)) \rightarrow F(a), x \mapsto a$ is an isomorphism. Its inverse is clearly the map sending $a$ back to $x$.

  • $\begingroup$ @Prometeheus I understand how you use the First Isomorphism Theorem. However, trying to prove directly that $g : \alpha \mapsto \overline{x} : F(\alpha) \to F[x]/(m(x))$ is an isomorphism, I don't see how the fact that $\alpha$ is a root of $m(x)$ is to be used. It seems to me that the way we define the map, i.e. $g(\displaystyle \sum_{i=0}^n a_i \alpha^i) := \displaystyle \sum_{i=0}^n a_i \overline{x}^i$, implies that we'll have $g(ab)=g(a)g(b)$, $g(a+b)=g(a)+g(b)$, $g(1)=1$ and surjectivity of $g$, for any $\alpha$ and $m(x)$. Hence it seems to me $g$ would be an isomorphism if $m(x)$ is.. $\endgroup$ – Amateur Sep 11 '14 at 3:30
  • $\begingroup$ .. taken to be irreducible and $\alpha$ not necessarily chosen to be a root of $m(x)$. However, in that case, $g(m(\alpha)) = \overline{m(x)} = 0$ seems to contradict injectivity ? $\endgroup$ – Amateur Sep 11 '14 at 3:33
  • 1
    $\begingroup$ The map $\alpha \mapsto \overline{x}$ would not be well-defined unless $\alpha$ is a root of $m(x)$. That's because relations satisfied in the domain must also be satisfied in the codomain. You have $m(\alpha)$ mapping to $\overline{m(x)}$, so if $m(\alpha)$ is zero, $\overline{m(x)}$ better be zero as well. $\endgroup$ – Prometheus Sep 11 '14 at 3:48
  • 1
    $\begingroup$ So whatever $\alpha$ maps to, must satisfy $p(x)$, otherwise we have $\phi(0)=0$ on the one hand from the fact that $\phi$ must a homomorphism, and on the other hand we'd have $\phi(0)=\phi(\alpha)\neq 0$. That means the map is not well-defined. Well-definedness is not really a technical term. Whenever you claim to define something and it turns out not to make sense, the thing is not well-defined. $\endgroup$ – Prometheus Sep 11 '14 at 4:08
  • 1
    $\begingroup$ I'm not sure what you are confused about then. You are claiming that $m(\alpha)=0$ is not used at all in the construction, but you are trying to show that by assuming it's not true, then deriving a contradiction. That just shows it must be true. $\endgroup$ – Prometheus Sep 11 '14 at 4:10

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.